Distribution of Thermodynamic Properties of the Atmosphere between 30 and 80 km - Cole, Allen E. (1972)
Recently acquired rocket observations from U.S. and USSR stations in arctic and subarctic regions were used to expand and update information published on extreme temperature, pressure, and density between 30 and 80 km. A revised set of estimated worldwide extremes of temperature, pressure and density are provided, together with frequency distributions of observed temperatures and densities at levels between 30 and 80 km for latitudes 30, 45, 60 and 80 deg N during June-July and December-January. Distributions around the annual mean are given for 15 deg N.